2015
DOI: 10.1007/s11109-015-9304-x
|View full text |Cite
|
Sign up to set email alerts
|

Does Enclave Deliberation Polarize Opinions?

Abstract: When like-minded people discuss with each other, i.e. engage in 'enclave deliberation', their opinions tend to become more extreme. This is called group polarization. A population-based experiment with a pre-test post-test design was conducted to analyze whether the norms and procedures of deliberation interfere with the mechanisms of group polarization. Based on a survey, people with either permissive or restrictive attitudes toward immigration were first identified and then invited to the experiment. The par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 122 publications
(137 citation statements)
references
References 30 publications
5
109
2
1
Order By: Relevance
“…The 207 individuals who eventually took part were randomly assigned to 26 small groups, which were either like-minded groups consisting of people from either the con or pro enclave or mixed groups with four participants from each enclave. The aim was for all groups to comprise eight participants, but as individuals from the con enclave abstained to a larger degree in the final recruitment phase, a few groups deviated from this principle (for more on the deliberative experiment and the procedures involved, see Grönlund et al, 2015).…”
Section: Data and Variablesmentioning
confidence: 99%
“…The 207 individuals who eventually took part were randomly assigned to 26 small groups, which were either like-minded groups consisting of people from either the con or pro enclave or mixed groups with four participants from each enclave. The aim was for all groups to comprise eight participants, but as individuals from the con enclave abstained to a larger degree in the final recruitment phase, a few groups deviated from this principle (for more on the deliberative experiment and the procedures involved, see Grönlund et al, 2015).…”
Section: Data and Variablesmentioning
confidence: 99%
“…Research about political processes such as referenda, deliberative panels, user boards and open political meetings, and how they are received by the general public has expanded in various ways, both in terms of survey and in terms of different forms of experimental research (Andersen & Hansen ; Bengtsson & Mattila ; Grönlund et al. 2010; 2015; Esaiasson et al. ; Persson et al.…”
Section: Publication Patterns and Research Themesmentioning
confidence: 99%
“…Inspired by signs of change in the way citizens engage in politics and negative trends in political trust and satisfaction with democracy (Grönlund & Setälä 2012;Holmberg 1999;Linde & Erlingsson 2013), there has also been lively discussion about how established democracies can expand the opportunities for citizens to participate in the political process, which has been inspired by theories of participatory and deliberative democracy (Demokratiutredningen 2000;Togeby et al 2003). Research about political processes such as referenda, deliberative panels, user boards and open political meetings, and how they are received by the general public has expanded in various ways, both in terms of survey and in terms of different forms of experimental research (Andersen & Hansen 2007;Bengtsson & Mattila 2009;Grönlund et al 2010;2015;Esaiasson et al 2012;Persson et al 2013a).…”
Section: Exceptional Democracies?mentioning
confidence: 99%
“…Sunstein (2002Sunstein ( , 2007Sunstein ( , 2009 argues that discussion in like-minded groups leads to opinion polarization, whereby opinions become more extreme, as well as to an amplification of cognitive errors. On the other hand, studies based on deliberative mini-publics have shown that the influence of like-mindedness on polarization can be alleviated when discussion takes place in a deliberative setting, where small group discussions are facilitated and primed by rules of discussion (Grönlund, Herne, and Setälä 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Further, we explore how differences in the deliberative settings influence the association between knowledge and polarization. Our research thereby combines two so far separate strands of literature, one on the connection between knowledge and polarization (Taber and Lodge 2006;Taber, Cann, and Kucsova 2009;Meffert et al 2006;Baekgaard et al 2017) and the other on the connection between deliberative democracy and polarization (Sunstein 2007;Grönlund, Herne, and Setälä 2015).…”
Section: Introductionmentioning
confidence: 99%